FINANCIAL PERFORMANCE AND HOSPITAL SERVICE PERFORMANCE IN PANDEMI TIME - Tulus Manurung; Adam Afiezan; Virna Natasya Angeli Siburian; Pesta Maria Pasaribu; Keulana Erwin (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Background : Different approaches that have been executed during the pandemic have brought about diminished execution and expanded clinic spending. This exploration was led to take a gander at viewpoints that adversely affect the exhibition of the Regal Prima Medan emergency clinic during a pandemic by utilizing monetary execution comprising of Liquidity, Dissolvability, Benefit and administration execution, specifically Bor, Toi and Gdr, with this proportion you can figure out how medical clinic execution during a pandemic both concerning monetary execution and administration execution. Method : The exploration led is a quantitative examination. Acquiring the examination test was helped out through non-likelihood inspecting, to be specific soaked testing. Result : The investigation completed is the old style presumption test which comprises of ordinariness test, multicollinearity, autocorrelation, heteroscedasticity, speculation assurance coefficient, F test, T test. Dissolvability, Benefit, Gdr boundaries make a fundamentally sure difference, Liquidity, Bor and Toi boundaries have an adverse consequence essentially on the exhibition of the Illustrious Prima Medan Clinic in 2018-2021. Conclusion : Execution results are supposed to be great or not, this is tracked down in that frame of mind as per the service of wellbeing which incorporates focuses as per execution results at the Illustrious Prima Medan clinic